Medical Regulation, Fitness to Practice and Revalidation : A Critical Introduction - Chamberlain, John Martyn (Book collections on Project MUSE., 2015)
Medical sociology has long been concerned with the role played by specialist forms of expertise in enabling the governance of 'troublesome' social groups - including those who are unwell, 'deviant' and criminally insane. However, only recently has it begun to explore how the state ensures the public is protected from acts of medical malpractice, negligence and criminality. Against the background of a series of high-profile scandals, including the case of Dr Harold Shipman who murdered over 200 of his patients, this topical and authoritative book examines how the regulation of doctors has been modernised by reforms to the Medical Practitioners Tribunal Service and the introduction of the quality assurance process of medical revalidation. In doing so, it questions whether there is evidence to support the argument that revalidation serves the public interest by ensuring that individual doctors are fit to practise. Highlighting areas of good practice and areas for further research and development, the book is ideal for academics and postgraduates interested in medical sociology, socio-legal studies, medical law, medical education, health policy and related subjects.